La desmemoria en la historia oficial : reflexiones sobre la memoria y el olvido en el exilio español - Mérida Donoso, José Antonio (Acta Hispanica, 2012)
The concepts of (collective) memory and history are similar in that they both deal with the notion of identity, yet diverge in their methods and dwell on the past events in different ways. History has now started to be regarded as an objective - a doubtful, though desirable attribute - "human" or "social" science, while memory remains the space of subjective experience. This article presents a series of reflections on Spain’s recent past, focusing on the role of literature in preserving the collective memory and constructing a social identity.